LBP-CD155 Liposome Nanovaccine Efficiently Resist Colorectal Cancer and Enhance ICB Therapy - Yan Y; Duan T; Xue X; Yang X; Liu M; Ma B; Duan X; Su C (International Journal of Nanomedicine)
Yajuan Yan,1,* Ting Duan,1,* Xiaonan Xue,1,* Xiaojuan Yang,2 Miao Liu,2 Bin Ma,3,4 Xiangguo Duan,2 Chunxia Su1 1Department of Basic Medicine, Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China; 2Department of Inspection, Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China; 3Department of Surgery, The First People’s Hospital of Yinchuan, Yinchuan, Ningxia, People’s Republic of China; 4The Second School of Clinical Medicine, Ningxia Medical University, Yinchuan, 750004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunxia Su; Xiangguo Duan, Email chunxiasu@qq.com; duanxiangguo@nxmu.edu.cnBackground: Colorectal cancer (CRC) is a highly malignant and aggressive gastrointestinal tumor. Due to its weak immunogenicity and limited immune, cell infiltration lead to ineffective clinical outcomes. Therefore, to improve the current prophylaxis and treatment scheme, offering a favorable strategy efficient against CRC is urgently needed.Methods: Here, we developed a nanovaccine (LBP-CD155L NVs) loaded with CD155 gene in liposome, which was modified by Lycium barbarum polysaccharides (LBP) through electrostatic interaction. The nanovaccine was characterized by transmission electron microscopy and Zetasizer. It was evaluated in vitro, where NVs facilitated the endocytosis and maturation of DCs, and in vivo, where NVs improved the efficacy of prophylaxis and therapy. In addition, further confirmed the mechanisms by how TLR4 and MGL synergistic pathway endow the nanovaccines towards dendritic cells (DCs). Finally, the safety and tumor immunosuppressive microenvironment were evaluated in the CRC tumor-bearing mouse model.Results: We successfully developed a nanovaccine that facilitates the endocytosis and maturation of DCs via a synergistic pathway involving TLR4 and MGL, which endow the nanovaccines towards dendritic cells (DCs) and promote the differentiation, thereby enhancing the cytotoxicity of CD8+T cells. Consequently, LBP-CD155L NVs can potentiate the efficacy of prophylactic and therapeutic administration in a mouse CRC model, as evidenced by decreased infiltration of myeloid-derived suppressor cells (MDSCs) and Tregs, reprogrammed the macrophage phenotypes, which promoted polarization from M2-like macrophages to M1-like macrophages, increased infiltration of effector T cells. Prophylactic and therapeutic combination regimens with anti-PD-1 treatment demonstrate synergism that stimulates T-cell infiltration into tumors and counteracts immunosuppression, leading to remarkable tumor remission and enhancing the efficacy of immune checkpoint therapy in solid tumors.Conclusion: Our work provided that LBP-CD155L NVs may serve as a promising tool for reversing tumor immunosuppressive microenvironment and enhancing ICB therapy in CRC.Keywords: Lycium barbarum polysaccharides, nanovaccines, nanovaccine codelivery, CD155, tumor immunotherapy